Analysis of Factors of Economics Lecturers of Stain Madina in Making Decisions to Saving in Syariah Banks (Case Study of Stain Mandailing Natal Lecturers) - Salsabila, Aidina (AMK : Abdi Masyarakat UIKA, 2024)
The main problem of this thesis is the use of Islamic banking in the daily lives of Economics Lecturers at STAIN Mandailing Natal. This study aims to determine and describe the factors underlying Economics Lecturers at STAIN Mandailing Natal in making decisions to save at Islamic banks. This type of research uses field research (Field Research) which is descriptive qualitative. The study uses two data sources, namely primary data and secondary data, as well as data collection techniques through interviews with Islamic Economics Lecturers, Islamic Banking Lecturers, and Islamic Business Management Lecturers at STAIN Mandailing Natal and also uses documentation as evidence of having conducted research. Then according to the data, it is analyzed inductively. Based on the results of the study, it can be concluded that Economics Lecturers at STAIN Mandailing Natal in making decisions to save at Islamic banks because of, religiosity factors, profit factors, service factors, promotion factors, location factors, and facility factors. and the most dominant factors in making decisions to save at Islamic banks are religiosity factors, facility factors and service factors. And the researcher concluded that the researcher interviewed 14 lecturers of Economics, the economics lecturers saving in Islamic banks was influenced by the religiosity factor of the bank as many as 8 lecturers and the bank facility factor as many as 4 lecturers and the service factor as many as 2 lecturers.